Dengue vector-control services: how do they work?: a systematic literature review and country case studies - Horstick, Olaf; Runge-Ranzinger, Silvia; Nathan, Michael B.; Kroeger, Axel (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2010)
The increasing incidence and geographic expansion of dengue suggest limitations of vector-control operations. We undertook an analysis of services with two methods: a systematic literature review; and case studies (stakeholder interviews, questionnaires) in Brazil, Guatemala, The Philippines and Viet Nam. In the systematic literature review there were only a few studies (strict criteria, 9 studies; less strict criteria, a further 16 studies and 3 guidelines). Of the 9 studies, 3 showed little change of control operations over time but did show strategic changes (decentralisation, intersectoral collaboration). Staffing levels, capacity building, management and organisation, funding and community engagement were insufficient. The case studies confirmed most of this information: (1) a lack of personnel (entomologists, social scientists, operational vector-control staff); (2) a lack of technical expertise at decentralised levels of services; (3) insufficient budgets; (4) inadequate geographical coverage; (5) interventions relying mostly on insecticides; (6) difficulties in engaging communities; (7) little capacity building; (8) almost no monitoring and evaluation. Stakeholders' doubts about service effectiveness were widespread, but interventions were assumed to be effective with increased resources. The analysis underlined the need for: operational standards; evidence-based selection/delivery of combinations of interventions; development/application of monitoring and evaluation tools; needs-driven capacity building.